2017
DOI: 10.1097/pra.0000000000000255
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Length of Stay in a Psychiatric Adolescent Treatment Program

Abstract: Understanding predictors of adolescent inpatient length of stay (LOS) is important in informing treatment outcomes for this age group. The current literature on adolescent LOS remains limited and has been characterized by methodological limitations. In the study described here, we examined a wide range of predictors for LOS in a psychiatric unit for adolescents (N=285), including severity of disorder (previous hospitalizations, self-harm, cognitive impairment and thought disorder, severe depression, history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…These patients were mainly diagnosed with psychotic spectrum disorders and mood disorders, predominantly mania [ 11 ]. A previous study showed that the length of stay in psychiatric inpatient youth clinics is associated with psychiatric severity, as reflected by prescription of mood stabilizers and self-reports of internalizing symptoms [ 12 ]. The use of restrictive measures, such as restraints and seclusion, are prevalent in youth psychiatric wards worldwide when managing patients at risk of harming themselves and/or others [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These patients were mainly diagnosed with psychotic spectrum disorders and mood disorders, predominantly mania [ 11 ]. A previous study showed that the length of stay in psychiatric inpatient youth clinics is associated with psychiatric severity, as reflected by prescription of mood stabilizers and self-reports of internalizing symptoms [ 12 ]. The use of restrictive measures, such as restraints and seclusion, are prevalent in youth psychiatric wards worldwide when managing patients at risk of harming themselves and/or others [ 13 ].…”
Section: Introductionmentioning
confidence: 99%